What difference does school leadership make to student outcomes?. Issue 2 (3rd April 2019) - Robinson, Viviane; Gray, Emma
ABSTRACT: Although it is widely believed by parents and policy makers that the quality of school leadership makes a difference to what students learn at school, testing this hypothesis has proved very complex. Part of the problem is the unreliability of many measures of leadership quality. In addition, the field has been dominated until quite recently by abstract theories of leadership which are not closely aligned to the specific work of educational leaders. While recent research by economists has confirmed that school leadership makes a significant difference to student outcomes, their analyses beg the question of how these effects are produced. In this article we address this question by updating the first author's 2008 model of student-centred leadership which identified the average impact of five sets of leadership practices on student outcomes. We argue that future research programmes should develop theories and measures of educational leadership which are based on expert judgments of the quality of enactment of these five sets of practices, and test their impact on a wider range of student outcomes.